Formulation and In Vivo Evaluation of Trilayer Matrix Tablets of Rosuvastatin Solid Dispersions by Geomatrix Technology (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
The current research is aimed at enhancing the aqueous solubility and sustains the drug release of rosuvastatin BCS Class II drug. 15 solid dispersion (SD) formulations of rosuvastatin prepared by solvent evaporation technique and evaluated. In vitro drug dissolution study indicated higher drug dissolution rate for SD13 of 99.74±5.39 % within 60 min. Eight formulations of rosuvastatin trilayer matrix tablets (AF10-HF10) were prepared by incorporating optimized SD13 by direct compression method. These trilayer formulations characterized for flow properties and physicochemical parameters. The maximum drug release was exhibited by trilayer matrix formulation (HF10) of 99.48±5.40 % over a period of 24 h. The release profile of the optimized formulation (HF10) was described by the zero order and best fitted to Higuchi and Korsmeyer-Peppa’s model. The results demonstrated the sustainability of rosuvastatin trilayer tablets with enhanced release time and linearity upto 24 h. From in vivo bioavailability studies Cmax of the rosuvastatin optimized ER tablets and marketed product was found to be 28.46±0.07 ng/mL and 30.94±0.75 ng/mL respectively. Tmax of both rosuvastatin optimized ER tablets formulation and rosuvastatin marketed product was 5±0.06 and 4±0.03 h, respectively. AUC0-∞ infinity for optimised formulation was higher (395.54±1.37 ng.h/ml) than the rosuvastatin marketed product formulation 212.54±0.42 ng.h/ml. Statistically, AUC0-t of the optimized ER tablets formulation was significantly higher (p<0.05) as compared to rosuvastatin marketed product formulation. In vivo pharmacokinetic studies in rabbits confirmed the prolonged release by showing increase in bioavailability for Rosuvastatin from optimized ER tablets than marketed formulation.